Effect of internet drawbacks on moral and social values of users in education - Hameed, Shihab A. (INSI Publications, 2011)
In this era of computer and knowledge; the moral and social values have essential affects on people and education process in the society. Internet, mobility and multimedia are important information technology tools that are used in education industry. Internet has an important effect on students, researchers, academic staffs, non-academic staffs and education process. Although Internet has an appreciated role in enhancing education process but it still has some drawbacks and harmful impacts that affected this role such as slow data accessing, retrieving to a huge volume of related data, existence of not trusted and harmful information, have bad impact on ethical, religious and social concerns. This paper is an analytical survey to study: the drawbacks of internet that affects moral and social aspects of internet users in university. To solve the problem, the paper proposes a Smart Data Filtration (SDF) tool. It is a data mining and fire-wall supporting tool, which has the ability to filter harmful data according to rules and regulations related to moral, religious, and social concerns. This tool will lead to enhance the internet usage and performance in education.